2018
DOI: 10.1016/j.ajhg.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent, Activating Variants in the Receptor Tyrosine Kinase DDR2 Cause Warburg-Cinotti Syndrome

Abstract: We have investigated a distinct disorder with progressive corneal neovascularization, keloid formation, chronic skin ulcers, wasting of subcutaneous tissue, flexion contractures of the fingers, and acro-osteolysis. In six affected individuals from four families, we found one of two recurrent variants in discoidin domain receptor tyrosine kinase 2 (DDR2): c.1829T>C (p.Leu610Pro) or c.2219A>G (p.Tyr740Cys). DDR2 encodes a collagen-responsive receptor tyrosine kinase that regulates connective-tissue formation. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…net/) (29) and off-targets were excluded using GT-Scan tools (30). Oligonucleotides with BsmB1 restriction sites for guide RNAs were synthesized by SBS Genetech Co., Ltd., then phosphorylated using T4 kinase (31). The phosphorylated oligonucleotides were cloned into LentiCRISPR v2 (Plasmid no.…”
Section: Bioinformatic Analysis For Analysis Of Gene Expressionmentioning
confidence: 99%
“…net/) (29) and off-targets were excluded using GT-Scan tools (30). Oligonucleotides with BsmB1 restriction sites for guide RNAs were synthesized by SBS Genetech Co., Ltd., then phosphorylated using T4 kinase (31). The phosphorylated oligonucleotides were cloned into LentiCRISPR v2 (Plasmid no.…”
Section: Bioinformatic Analysis For Analysis Of Gene Expressionmentioning
confidence: 99%
“…Moreover, DDR2 expression is stimulated by the angiogenic growth factor VEGF. The role of DDR2 in angiogenesis was further demonstrated in the presentation by Cecilie Bredrup (Haukeland University Hospital, Bergen, Norway), who found that the L610P and Y740C mutations constitutively activate DDR2 and induce the angiogenic defect seen in Warburg-Cinotti syndrome (Xu et al, 2018). Finally, Yi-Chun Yeh (National Cheng Kung University, Tainan, Taiwan) showed that in kidney, DDR1 promotes epithelial cell differentiation by stabilizing E-cadherin at cell-cell junctions (Chen et al, 2016).…”
Section: Ddrs In Physiology and Diseases Other Than Cancermentioning
confidence: 93%
“…Autosomal dominant variants in the parathyroid hormone-like hormone (PTHLH) gene, which is important in mediating bone homeostasis, can result in a syndrome characterized by acro-osteolysis, cortical irregularity of long bones and metadiaphyseal enchondromata [ 10 ]. Autosomal dominant Warburg-Cinotti syndrome due to variants in discoidin domain receptor tyrosine kinase 2 (DDR2) is associated with progressive corneal vascularization, keloid formation, chronic skin ulcers, wasting of subcutaneous tissue, flexion contractures of the fingers, and acro-osteolysis [ 11 ]. Autosomal dominant Singleton-Merten syndrome is an interferonopathy characterized by variable expression of aortic calcification, dental anomalies, osteopenia and acro-osteolysis, and to a lesser degree glaucoma, psoriasis, muscle weakness and joint laxity [ 12 ].…”
Section: Methodsmentioning
confidence: 99%